Pelvic ring reconstruction with double‐barreled fibular free flap: A systematic review. Issue 3 (9th September 2021) - Bastoni, Stefano; Lucattelli, Elena; Cipriani, Federico; Cannamela, Giacomo; Innocenti, Marco; Menichini, Giulio
Abstract: Introduction: Pelvic ring reconstruction after internal hemipelvectomy is an extremely challenging surgical procedure, and mandatory reconstruction is to provide a durable and pain‐free functional outcome, especially for young, active patients. One of the most widely employed techniques is reconstruction with a double‐barreled fibular free flap (DBF). The aim of our work was an in‐depth analysis of the outcome of pelvic ring reconstruction performed using the above‐mentioned method, in particular looking for a correlation between the fixation technique and either ambulation status or complications. Materials and methods: A systematic review was performed in November 2020 using PubMed and MedLine Ovid databases according to the PRISMA guidelines and the results were statistically analyzed. Results: Studies were published between 1994 and 2015. A DBF was used in each case, with a total of 30 patients. Reconstruction was performed with screws in 13 cases, Cotrel‐Dubousset rod fixation in 6, screws and plate in 5, screws with external fixation in 4, and ISOLA in 2. Follow‐up time ranged from 3 to 131 months. Functional outcome was excellent in 4 patients and good in 26 patients. Statistical analysis showed no statistical evidence of existing correlation between fixation technique and complications ( p  = .873), while statistical correlation between age and fixation technique was found ( p  < .001). Conclusion: Reconstruction of pelvic ring with DBF provides an overall good functional outcome. Our data indicate that there is no statistical evidence of existing correlation between the fixation technique and either complications or ambulation status.